Imaging and the Value of the Pediatric Appendicitis Score for Diagnosis of Acute Appendicitis in the Pediatric Emergency Department - Tuğçe NALBANT; Gamze GÖKALP; Yüksel BİCİLİOĞLU; Emine Burcu ÇIĞŞAR KUZU; Esin ERGÖNÜL (Forbes Tıp Dergisi)
Objective: Acute appendicitis (AA) is a common cause of acute abdominal pain in pediatric patients. The diagnosis of AA in children can sometimes be difficult to make accurately. For this reason, ultrasonography (US) and computed tomography (CT) are also commonly used methods for diagnosis. Scoring systems such as the pediatric appendicitis score (PAS) have gained attention because they integrate multiple clinical and laboratory parameters to help predict AA. The aim of this study was to evaluate the efficacy of various clinical, laboratory, and imaging parameters in diagnosing appendicitis in children and to determine which factors are most predictive for accurate diagnosis. Methods: The study included 153 patients who presented to the pediatric emergency department with abdominal pain and were operated on for AA. PAS was calculated for each case. Patients were divided into two groups as “appendicitis” and “non-appendicitis” according to pathology results. Results: The positive predictive value and negative predictive value of US in the diagnosis of appendicitis were found to be 60% and 87%, respectively, while CT showed higher accuracy rates with 86% sensitivity and 97% specificity. Logistic regression modeling to investigate which parameters influence the histomorphologic diagnosis of appendicitis revealed that younger age increased the likelihood of appendicitis by 4.29-fold, high white blood cell increased it by 5.44-fold, high PAS increased it by 7.87-fold, and diagnostic US increased it by 7.91-fold. Conclusion: The study suggests that the combination of laboratory tests and imaging modalities can improve the accuracy of appendicitis diagnosis, especially in children, and prevent unnecessary surgery.